2005
DOI: 10.1002/hep.20885
|View full text |Cite
|
Sign up to set email alerts
|

Early intrahepatic antigen-specific retention of naïve CD8+T cells is predominantly ICAM-1/LFA-1 dependent in mice

Abstract: We have previously shown that naïve CD8 ؉ T cells recognizing their cognate antigen within the liver are retained and undergo activation in situ, independent from lymphoid tissues. Intrahepatic primary T cell activation results in apoptosis and may play a crucial role in the ability of the liver to induce tolerance. Although adhesion molecules required for intrahepatic retention of T cells that have undergone previous extra-hepatic activation have been characterized, adhesive interactions involved in selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
2
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 44 publications
6
46
2
2
Order By: Relevance
“…5A), a result consistent with flow cytometric and radiolabeling studies 6,27 ; V. Benseler and P. Bertolino unpublished result). Most of the donor T lymphocytes (93%) were found in the sinusoids rather than in portal tracts (Fig.…”
Section: Ihl Interact With Hepatocytes Through Fenestrations In Lsecssupporting
confidence: 83%
“…5A), a result consistent with flow cytometric and radiolabeling studies 6,27 ; V. Benseler and P. Bertolino unpublished result). Most of the donor T lymphocytes (93%) were found in the sinusoids rather than in portal tracts (Fig.…”
Section: Ihl Interact With Hepatocytes Through Fenestrations In Lsecssupporting
confidence: 83%
“…Analogous to our study, mice infected with LM (38), EBV, cytomegalovirus (70), and hepatitis A virus (15) showed enrichment of Ag-specific T cells within the liver CD8 ϩ T cell population. Selective retention of activated CD8 ϩ T cells in the liver has been attributed to trapping mediated primarily by ICAM-1 constitutively expressed on sinusoidal endothelium and Kupffer cells (13,71). In the present analysis, the liver, lung, and BAL CD8 ϩ populations showed similar proportions of influenza-specific T cells.…”
Section: Discussionsupporting
confidence: 57%
“…3), which is in contrast to intrahepatic T-cell retention in response to ubiquitously presented antigen. 10 However, the contribution of chemokines to antigen-specific CD8 T-cell retention in the liver still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated CD8 T-cell tolerance toward circulating antigens. However, these studies used minimal MHCbinding peptides 2 or endogenous antigens, 10,11 and thus failed to consider that exogenous circulating protein antigens require cross-presentation for recognition by CD8 T-cells. We have previously reported that LSECs upon adoptive transfer can cross-present antigen to naïve CD8 T-cells initiating T-cell tolerance rather than immunity.…”
mentioning
confidence: 99%